Estimating Real Income in the United States from 1888 to 1994: Correcting CPI Bias Using Engel Curves - Costa, Dora L. (Journal of Political Economy, 2001)
This paper provides the first estimates of overall CPI bias prior to the 1970s and new estimates of bias since the 1970s. It finds that annual CPI bias was −0.1 percent between 1888 and 1919 and rose to 0.7 percent between 1919 and 1935. Annual CPI bias was 0.4 percent in the 1960s and then rose to 2.7 percent between 1972 and 1982 before falling to 0.6 percent between 1982 and 1994. The findings imply that we have underestimated growth rates in true income in the 1920s and 1930s and in the 1970s.